Differences in Ambient Polycyclic Aromatic Hydrocarbon Concentrations between Streets and Alleys in New York City: Open Space vs. Semi-Closed Space - Stephanie Lovinsky-Desir (International Journal of Environmental Research and Public Health, 2016)
Background: Outdoor ambient polycyclic aromatic hydrocarbon (PAH) concentrations are variable throughout an urban environment. However, little is known about how variation in semivolatile and nonvolatile PAHs related to the built environment (open space vs. semi-closed space) contributes to differences in concentrations. Methods: We simultaneously collected 14, two-week samples of PAHs from the outside of windows facing the front (adjacent to the street) open side of a New York City apartment building and the alley, semi-closed side of the same apartment unit between 2007 and 2012. We also analyzed samples of PAHs measured from 35 homes across Northern Manhattan and the Bronx, 17 from street facing windows with a median floor level of 4 (range 2–26) and 18 from alley-facing windows with a median floor level of 4 (range 1–15). Results: Levels of nonvolatile ambient PAHs were significantly higher when measured from a window adjacent to a street (an open space), compared to a window 30 feet away, adjacent to an alley (a semi-closed space) (street geometric mean (GM) 1.32 ng/m3, arithmetic mean ± standard deviation (AM ± SD) 1.61 ± 1.04 ng/m3; alley GM 1.10 ng/m3, AM ± SD 1.37 ± 0.94 ng/m3). In the neighborhood-wide comparison, nonvolatile PAHs were also significantly higher when measured adjacent to streets compared with adjacent to alley sides of apartment buildings (street GM 1.10 ng/m3, AM ± SD 1.46 ± 1.24 ng/m3; alley GM 0.61 ng/m3, AM ± SD 0.81 ± 0.80 ng/m3), but not semivolatile PAHs. Conclusions: Ambient PAHs, nonvolatile PAHs in particular, are significantly higher when measured from a window adjacent to a street compared to a window adjacent to an alley, despite both locations being relatively close to street traffic. This study highlights small-scale spatial variations in ambient PAH concentrations that may be related to the built environment (open space vs. semi-closed space) from which the samples are measured, as well as the relative distance from street traffic, that could impact accurate personal exposure assessments.